Low-temperature plasma treatment for hydrophobicity improvement of silk - Chaivan P. (2014)
This paper describes the development of a plasma system for textile treatment. The SF6 plasma was applied to improve hydrophobic property of Thai silk. It was produced by an inductively coupled 13.56 MHz RF discharge in a cylindrical stainless steel chamber of 31.2 cm diameter and 42.5 cm long. The plasma was confined by arrays of permanent magnet buttons. The operating pressure was at 1, 3, 5 and 7 mTorr while the RF power was varied from 25 to 75 W. The plasma parameters were characterized by two techniques, the single movable Langmuir probe and optical emission spectroscopy (OES). The absorption times and contact angles were utilized to analyze the result of the treated sample. The SF6 plasma parameters were measured at the center of the chamber. The electron temperature was about 3-5 eV and the ion density was 1.0-3.5×1010 cm-3. The optical emission spectroscopy results show the mixture of fluorine ion inside the plasma. The hydrophobicity improvement of silk was achieved. The treated samples reach the limit of the absorption times at 180 min and increase the contact angle to 130-140°. These results show a significant increase in the hydrophobic property compared with the untreated sample. The optimum operating conditions were at an RF power of around 50 W and a pressure of 3-5 mTorr. © 2004 Elsevier B.V. All rights reserved.